Analysis of disruption factors at PT PLN Indonesia Power PLTU Banten 2 Labuan PGU using a grounded theory approach and pareto analysis of lean kaizen - Sembodo, Giry; Praditya, Rizqy Gumilar; Sari, Nimas Indah Fatimah; Heikal, Jerry (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The reliable and efficient availability of electricity is a crucial factor in economic and social development. PT PLN (Persero), through its subsidiary PT PLN Indonesia Power, is responsible for providing electricity, including operating the 2x300 MW Banten 2 Labuan coal-fired power plant. However, in 2022, the Banten 2 Labuan plant experienced 28 disruptions, leading to a decrease in production capacity from 4,838.4 GWH to 4,259.716 GWH per year. This study aimed to identify the factors causing these disruptions and the decline in electricity production capacity. A qualitative approach using the Grounded Theory method was employed, involving in-depth interviews with the Assistant Manager of Operation Planning and Control, the Assistant Manager of Maintenance Planning and Control, and the Assistant Manager of Public Relations and CSR of the Banten 2 Labuan plant, as well as field observations and document studies. Through open coding, axial coding, and selective coding, three themes emerged as causes of disruption: internal factors (frequency 14), external factors (frequency 9), and force majeure (frequency 4). Pareto analysis revealed internal factors as the most dominant, contributing to 51.9% of the disruptions, with equipment failure (frequency 11) being the most significant internal factor, contributing 40.7% to the total disruptions. Consequently, optimization of maintenance strategies, improvement of human resource competencies, and the application of Lean Manufacturing principles, including Predictive Maintenance, Preventive Maintenance, Corrective Maintenance, and Breakdown Maintenance within the framework of Reliability Engineering and Maintenance Management, are necessary to enhance the operational reliability of the Banten 2 Labuan power plant.